Effects of Fermentation by Lactobacillus Plantarum on Chemical Composition and Functional Properties of Mung Bean - Yaddehige, Sachithra Kalhari; Anal, Anil Kumar; Datta, Avishek; Sadiq, Muhammad Bilal; Loc Thai Nguyen (Pathum Thani : Asian Institute of Technology, 2018)
Pulses have commonly been the subject of many researches due to their potential applications in food, feed, pharmaceutics, biotechnology and medical applications. Pulses are the edible dry seeds obtained from legume plants. Mung bean (Vigna radiate) is a common legume family food crop in Asia. Though having high potential bioactive properties and high nutritional value, mung bean has still been underutilized in many countries around the world and only few investigations have been conducted. Probiotic carrying functional food has been the interest of many researches recently. Fermentation of the pulse mung bean, using lactic acid bacteria (LAB) is an interesting work area for the development of novel functional food. In this current research, a mung bean slurry was prepared and fermented with Lactobacillus plantarum without the addition of any supplements. The microbial populations, crude proteins, DPPH inhibitory activity and total phenolic compounds of fermented mung bean were investigated. One-way analysis of variance (ANOVA) showed that fermentation influenced the LAB population, reducing sugars, pH, acidity, proteins, antioxidant activity and TPC of mung bean. The optimized inoculum 4% gave the highest LAB population which was 8.893 log cfu/mL at 6 hours of fermentation. Kjeldahl results showed that most of the mung bean proteins have been degraded during the process of fermentation. Antioxidant activity as scavenging activity of 1,1- diphenyl-2-picrylhydrazyl (DPPH) radical showed that fermentation increases the antioxidant activity of raw mung bean giving the highest %inhibition of 20.54% at 12 hours of fermentation. The TPC of fermented mung bean was higher than that of raw mung bean, but it decreased with the increasing fermentation time. The highest TPC of 1.23 was resulted by the autoclaved but unfermented mung bean sample. Overall, the current study demonstrated that mung bean could be a resourceful LAB carrier and when mung bean is fermented by L. plantarum it has a great potential to be served as a functional novel food, and it also is suitable as a good starchy substrate to be used in the production of lactic acid. Also the current research shows that mung bean can be used as functional food which is also carrying probiotics which can be used to replace dairy probiotic food products so lactose intolerance people can ingest probiotics with their food.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Biosystems Engineering
Capstone Project (B.Sc.)-Asian Institute of Technology, 2018
Keywords: Mung bean; Lactobacillus plantarum; Fermentation; Probiotics